Maximizing safe passage for large fish: Evaluating survival of rainbow trout through a novel hydropower turbine - Brett D. Pflugrath; Robert P. Mueller; Katherine A. Deters; Sterling M. Watson; Abraham D. Schneider; Zhiqun Daniel Deng (Environmental and Sustainability Indicators, 2025)
As hydropower continues to play an important role in renewable energy production, there is a continuing need to mitigate or eliminate the negative effects of hydropower on fish populations. This study examined a novel hydropower turbine (Restoration Hydro Turbine) designed to maximize safe passage with survival rates exceeding 99 %. Tests using adult hatchery-reared rainbow trout (Oncorhynchus mykiss) were performed over two trial periods, one in 2020 and the other in 2022, at the Monroe Drop Facility in Jefferson County, Oregon. Of the 166 treatment and 141 control fish tested over the two years (fork length 200–530 mm, mass 305.0–1225.5 g), no immediate mortalities or major injuries were observed. The results of this study indicate a very high likelihood of immediate survival (100 % in 2020, 98.6 % in 2022) for rainbow trout in the size range examined when passing through the turbine. The absence of major injuries and mortalities attributable to turbine passage demonstrates the potential of novel turbine designs to minimize fish injury during hydropower generation.